Hasil Tangkapan Bubu Dasar Tradisional Dan Modern Yang Dioperasikan Di Perairan Sungai Wakante Kecamatan Lawa, Kabupaten Muna Barat - Umar, Umar; Alimina, Naslina; Arami, Hasnia; Mustafa, Ahmad; Abdullah, Abdullah; Tadjuddah, Muslim (Universitas halu Oleo, 2024)
This research aims to identify fish type, fish length, and total catch differences of bottom traps operated in the Wakante River, Lawa District, Muna Barat. The research was carried out from April to May 2023. The method used was experimental fishing by 20 trips bottom traps operation. The data collected includes the design and specifications of fishing gear, fish type, fish individual length, and the number of individuals caught of every trip. The result of the research shows that there were 5 types of fish in both traditional and modern trap name three spot cichlid (Amphilopus sp.), mozambique tilapia (O. niloticus), nile tilapia (O. mosambicus), three spot gourami (T. trichopterus), and silver barb (B. gonionotus). Besides that, there is one type of freshwater crabs (Terrathelupsa sp.) which is caught in modern traps. Fish length caught of both fishing gears was dominated by fish longer than Lm, with a proportion around 55.17% of traditional traps and 58.64% of modern traps. Based on the result of statistical analysis, there is no number differences of catch between traditional and modern traps.